O trabalho com a escrita de textos em livros didáticos de português: escolarização de saberes lingüísticos - Mariana Queiroga Tabosa (2008)
This research aims to comprehend how the work with the writing of texts happens in three Portuguese didactic books, from the relationship of conversation that establishes with awareness of reference of the Linguistic, texts of official curricula, and programs of assessment of didactic materials of national coverage. The didactic books chosen are from the eighth level of the secondary education, published in the last three decades, especially in the years of 1984, 1998 and 2002. The analyses of these books take place from the procedures of textual analysis purposed by the Content Analysis and the Analysis of the Speech, considering the relationship between the organization of the speeches and their production conditions. These analyses are organized in two stages. The first one refers to the analysis of the language conceptions presented by the Teacher Guide of the didactic books. In the second one, it is studied the work (the activities) proposals with the language and with the writing of texts, present in the Students Book, showing the relationship that establish with the language conceptions, present in the Teachers Guide. The two stages of the analyses go through the identification of linguistic awareness of reference, and of their ways of schooling, that, as it can be seen, happens in an indirect manner, especially from texts of official curricula (curricular proposals and parameters) and criteria defined by the assessment programs of didactic materials (National Programs of Didactic Books - NPDB). In such sense, it has in view to make clear the dynamic of reference which establishes itself between the proposals for the Portuguese Teaching of didactic books, and the Linguistic awareness. The accomplished study demonstrated that there is an alternation of the language conceptions and of the way of purposing the work with the writing of texts, which sometimes happens from orientations which suggest the language conception as an instrument for the communication, sometimes happens from the orientations that bring, in an underlying way, the language conception as social interaction. In such sense, the schooling of linguistic awareness happens, in the Students Book, especially from the utilization of terminologies that refers to the language conceptions as instrument for the communication or the language as social interaction.